Anticyanobacterial effect of l-lysine on Microcystis aeruginosa. Issue 38 (13th June 2018) - Tian, Lili; Chen, Meng; Ren, Chongyang; Wang, Yiying; Li, Li
Abstract : l -lysine had an anticyanobacterial effect on Microcystis aeruginosa, which involved growth inhibition, physiological and metabolic disturbance, and cell membrane damage. Abstract : Cyanobacterial blooms can cause serious environmental problems and threaten aquatic organisms and human health. It is therefore essential to effectively control cyanobacterial blooms in aquatic ecosystems. In the present study, the anticyanobacterial effect ofl -lysine on Microcystis aeruginosa was examined. The results showed that the growth of M. aeruginosa (>90%) was effectively inhibited byl -lysine at dosages of 5.0, 6.5, and 8.0 mg L −1 after 3 d treatment. The content of superoxide anion radicals, MDA content and SOD activity in M. aeruginosa cells increased after 1 d of treatment withl -lysine (3.0, 5.0, 6.5, and 8.0 mg L −1 ), revealing thatl -lysine induced oxidative stress in the cyanobacterial cells. The chlorophyll- a and protein contents in M. aeruginosa treated withl -lysine (3.0, 5.0, 6.5, and 8.0 mg L −1 ) decreased after 2 d, indicating damage of the photosynthetic system byl -lysine treatment. Additionally, the production of exopolysaccharide by M. aeruginosa also increased and the expression of polysaccharide synthesis genes was upregulated by 3.0 mg L −1 l -lysine after 3 d of treatment. In response to the algicidal effects ofl -Lysine, M. aeruginosa upregulated exopolysaccharide synthesis. Electron microscopic observations demonstrated that the cell membrane of M. aeruginosa was broken down during treatment withl -lysine (≥3.0 mg L −1 ). Our results revealed that the effects ofl -lysine on M. aeruginosa cells were comprehensive, andl -lysine is therefore an efficient anticyanobacterial reagent.